CYBER SECURITY ISSUES CONFRONTING SCHOOL ADMINISTRATORS IN THE MANAGEMENT OF INFORMATION SYSTEM IN SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2025)
Digital information management systems have impacted critical technical infrastructure development around the world but cyber security management issues are constantly at the fore, therefore, the need to strengthen and protect these systems against the ever-evolving cyber threats is pertinent. The study therefore, analyzed cyber security issues confronting administrators in management information systems in the secondary schools in Anambra State. The study adopted descriptive survey design and two research questions guided the study. The population of the study is made 265 principals of the public secondary school in Anambra state. A researcher developed instrument titled ‘Cyber security Issues confronting secondary school administrators in management information system questionnaire” (CSICSSAMISQ) was use to collect data. The questionnaire containing 20 items, structured on 4 point liket structure of Strongly Agreed (SA), Agreed (A), Strongly Disagreed (SD), and Disagreed (D). It was validated by three experts who are lecturers in the department of Educational Management and policy and Measurement and Evaluation all in the Faculty of Education, Nnamdi Azikiwe University, Awka. Cronbach-alpha was used to test reliability of the instrument which yielded a coefficient value of 0.85. Data were analyzed using mean and standard deviation. The findings of the study showed that there are constant cyber threats on school information systems and cyber security measures have been applied minimally. Therefore, the study concluded that cyber-attack and threats are the bane of information technology and to mitigate this challenge, Administrators of school organizations have to be ahead of these attackers in making sure that all kinds of vulnerabilities and gaps are constantly closed in by applying multiple security measures. It was recommended that; the Administrators should organize periodic capacity building seminars and workshops for their Administrative Staff on digital information management and cyber security. Also Government should be proactive in prosecuting internet fraudsters. If all these are done, they will ensure a sustainable school information management system.
Keywords: Cyber-Security, Administrators, Management, Information, Systems